2014
DOI: 10.1111/bjh.13126
|View full text |Cite
|
Sign up to set email alerts
|

In vitro TNF blockade enhances ex vivo expansion of regulatory T cells in patients with immune thrombocytopenia

Abstract: Summary Tumour necrosis factor-α (TNF) is an inflammatory cytokine that is elevated in a number of autoimmune diseases including immune thrombocytopenia (ITP), a bleeding disorder characterized by low platelet counts. In vitro TNF blockade increases expansion of the regulatory T cell (Treg) IKZF2 (also termed Helios) subset in T cell-monocyte cocultures from healthy donors, but its role on proliferative responses of Tregs in ITP patients, who have altered immunoregulatory compartment, remains unclear. TNF in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…31 Additionally, TNF blockers may be effective in the treatment of patients with ITP by increasing Treg proliferation. 32 Consistent with the results in RA reported by Cros et al 33 and Rossol et al, 26 we identified that the intermediate subset produces the highest level of TNF-a and IL-1b among the 3 subsets in patients with active ITP. After CR, the TNF-a secretion decreased rapidly, which suggests that the intermediate subset participates in the pathogenesis of ITP through an increased capability for cytokine secretion.…”
Section: Discussionsupporting
confidence: 91%
“…31 Additionally, TNF blockers may be effective in the treatment of patients with ITP by increasing Treg proliferation. 32 Consistent with the results in RA reported by Cros et al 33 and Rossol et al, 26 we identified that the intermediate subset produces the highest level of TNF-a and IL-1b among the 3 subsets in patients with active ITP. After CR, the TNF-a secretion decreased rapidly, which suggests that the intermediate subset participates in the pathogenesis of ITP through an increased capability for cytokine secretion.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the increase in IL‐10 + B cells as well as CD5 + B cells, which may represent overlapping subsets, is compatible with induction of Tregs. It can be speculated that the increase in IL‐6 + B cells after RTX+DXM treatment may support Treg development indirectly through downregulation of TNF that would otherwise inhibit Treg expansion …”
Section: Discussionmentioning
confidence: 99%
“…It can be speculated that the increase in IL-6 + B cells after RTX+DXM treatment may support Treg development indirectly through downregulation of TNF 35,36 that would otherwise inhibit Treg expansion. 49 A number of limitations apply to this study: First and foremost, frozen PBMCs were only available from 16 ITP patients. Therefore, the study can only be regarded as explorative.…”
Section: Association Between B-cell Subsets and Platelet Numbers Afmentioning
confidence: 99%
“…TNF is known to have widespread and profound effects on both the activation and the proliferation of different subsets of immune cells in several disease states. In vitro anti-TNF blockage, used in T-cell monocyte co-cultures of patients with the autoimmune disorder thrombocytopenia, produced a robust proliferation of the immunomodulatory regulatory T (Treg) cells 71 ; interestingly, this Treg cell expansion was dependent on TNFR2 and not TNFR1. Blockage of TNFR2 resulted in a robust expansion of Treg cells, whereas neutralisation of TNFR1 had no effect on this Treg cell expansion 71 .…”
Section: Cellular Activation and Proliferationmentioning
confidence: 99%